Fiscal Incentives and Firm Performance : Evidence from the Dominican Republic - Amendola, Alessandra (World Bank, Washington, DC, 2018)
This paper evaluates the impact of fiscal incentives on firm performance in the Dominican Republic. In recent years, the Dominican government has approved several new corporate tax benefits. While the literature on value-added tax incentives is extensive, the impact of corporate tax incentives is less well studied and is the subject of an ongoing debate. Using firm-level panel data from 2006 to 2015, this analysis uses fixed- and random-effects models to examine the relationship between corporate tax incentives and selected firm-level performance indicators. The results reveal that corporate income tax exemptions positively impact the performance of individual firms in the Dominican Republic, but uneven tax treatment across firms distorts competition in the industrial sector, with negative effects on overall economic productivity.